Landasan-Landasan Perkembangan Kurikulum Pendidikan Agama Islam (PAI) - Rahma Nabiilah Nuraniyyah; Riadah Amanda Damayanti; Selpi Dwi Ariani; Sultan Fassyadila Syarif; Syamil Sayyafi; Achmad Junaedi Sitika (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2026)
Curriculum is one of the important elements in the implementation of education, including in Islamic Religious Education (PAI). In the development process, curriculum cannot be compiled arbitrarily, but needs to be based on various foundations that can serve as a reference so that educational objectives can be achieved properly. This article discusses various bases that become the foundation for developing the PAI curriculum, namely philosophical, psychological, sociological, and juridical foundations. The philosophical foundation plays a role in providing direction and basic values of Islamic education sourced from the Qur'an and Hadith. The psychological foundation is related to the characteristics and stages of development of students so that learning materials and processes can be adjusted to their needs. Meanwhile, the sociological foundation emphasizes the importance of curriculum to answer the needs of society and ongoing social changes. Meanwhile, the juridical foundation serves as a guide so that the curriculum developed remains in accordance with applicable education regulations and policies. Through understanding of these four foundations, the development of the PAI curriculum is expected to be able to produce students who have strong faith, broad insights, and are able to contribute positively to social, national, and religious life. Kurikulum merupakan salah satu unsur penting dalam penyelenggaraan pendidikan, termasuk dalam Pendidikan Agama Islam (PAI). Dalam proses pengembangannya, kurikulum tidak dapat disusun secara asal, tetapi perlu didasarkan pada berbagai landasan yang dapat menjadi acuan agar tujuan pendidikan dapat tercapai dengan baik. Artikel ini membahas berbagai landasan yang menjadi dasar pengembangan kurikulum PAI, yaitu landasan filosofis, psikologis, sosiologis, dan yuridis. Landasan filosofis berperan dalam memberikan arah dan nilai dasar pendidikan Islam yang bersumber dari Al-Qur'an dan Hadis. Landasan psikologis berkaitan dengan karakteristik serta tahap perkembangan peserta didik sehingga materi dan proses pembelajaran dapat disesuaikan dengan kebutuhan mereka. Sementara itu, landasan sosiologis menekankan pentingnya kurikulum untuk menjawab kebutuhan masyarakat serta perubahan sosial yang terus berlangsung. Adapun landasan yuridis menjadi pedoman agar kurikulum yang dikembangkan tetap sesuai dengan peraturan dan kebijakan pendidikan yang berlaku. Melalui pemahaman terhadap keempat landasan tersebut, pengembangan kurikulum PAI diharapkan mampu menghasilkan peserta didik yang memiliki keimanan yang kuat, wawasan yang luas, serta mampu memberikan kontribusi positif bagi kehidupan bermasyarakat, berbangsa, dan beragama.